In Vivo Selection of Protease Cleavage Sites by Using Chimeric Sindbis Virus Libraries - Pacini, Laura (American Society for Microbiology, 2000)
Identifying protease cleavage sites contributes to our understanding of their specificity and biochemical properties and can help in designing specific inhibitors. One route to this end is the generation and screening of random libraries of cleavage sites. Both synthetic and phage-displayed libraries have been extensively used in vitro. We describe a novel system based on recombinant Sindbis virus which can be used to identify cleavage sites in vivo, thus eliminating the need for a purified enzyme and overcoming the problem of choosing the correct in vitro conditions. As a model we used the serine protease of the hepatitis C virus (HCV). We engineered the gene coding for this enzyme and two specific cleavage sites in the Sindbis virus structural gene and constructed libraries of viral genomes with a random sequence at either of the cleavage sites. The system was designed so that only viral genomes coding for sequences cleaved by the protease would produce viable viruses. With this system we selected viruses containing sequences mirroring those of the natural HCV protease substrates which were cleaved with comparable efficiencies.